Rezim Kebenaran dan Kuasa Negara: Analisis Wacana Kritis atas Kontroversi Kuota Haji Khalid Basalamah - Ikmal Maulana Akbar; Dzulfikar Adirais; Dono Darsono (AN-NASHIHA Journal of Broadcasting and Islamic Communication Studies, 2026)
This article analyzes the 2024 Hajj quota controversy involving Khalid Basalamah through the lens of Michel Foucault's theory of truth regimes. Using a Critical Discourse Analysis (CDA) approach, this study demonstrates how the state, bureaucracy, and digital media collectively produce "social truths" that do not always align with legal facts. Key findings demonstrate three discursive mechanisms at work: procedural normalization by the state bureaucracy, the production of social stigma through digital media framing, and the struggle for moral legitimacy in the public sphere. This case demonstrates that the Hajj pilgrimage has become a political-administrative arena where power operates subtly but effectively to shape public perception.